Electromechanical System for wheelchair elevation - do Carmo, Sidnei Lima de Oliveira (2019)
This project aimed at developing a prototype of an electromechanical device  to be adapted in a conventional wheelchair. So, the chair can be raised together with the wheelchair and, consequently, it may have access to objects that are located on top of furniture, shelves, among others, not only in public places but also at home, improving accessibility.